First-principle study of the effects of biaxial strain on the photocatalytic and magnetic mechanisms of ZnO with Sm doping and point defects (VZn, Hi). (July 2021) - Yang, Airong; Hou, Qingyu; Yin, Xiang; Sha, Shulin
Abstract: The influence of Sm doping on the physical properties of ZnO has been widely investigated. However, the potential point defects and interstitial H in the Sm-doped ZnO system and the influence of strain on the physical properties of ZnO remain poorly understood. First-principle studies on the effects of biaxial strain on the photocatalysis and magnetic mechanisms of ZnO with Sm doping and point defects (VZn, Hi ) are rarely reported. In this work, a method based on first-principle plane wave super soft pseudopotential + U under the framework of density functional theory was adopted. A ZnO system with Sm doping and point defects (VZn, Hi ) was constructed, and its formation energy, photocatalysis, and magnetic mechanism were studied within the strain range from −6% to 6%. Results showed that regardless of tensile/compressive strain, the formation energy increased in the doped system compared with that in the unstrained doped system. By contrast, stability was relatively decreased. Under the same strain conditions, the Zn34 SmHi O36 system had relatively low formation energy and relatively good stability. In addition, interstitial H can effectively increase the separation speed of electron–hole pairs, thereby prolonging the carrier life. Redshift effect, electric dipole moment, oxidation/reduction reactions, and decisive carrier lifetime are affected by the photocatalytic performance of the actual doping system. Under −4% compressive strain, the Zn34 SmHi O36 system acts as an excellent catalyst of light. Regardless of tensile/compressive strain, the Zn34 SmO36 and Zn34 SmHi O36 systems exhibit magnetic properties, and the interstitial H improves the magnetic properties of the doped system. This finding is consistent with the Ruderman–Kittel–Kasuya–Yosida (RKKY) magnetic theory. Under unstrained conditions, the Zn34 SmHi O36 system exhibits a semi-metallic characteristic with 100% hole spin polarization. This research has application value for the design and preparation of novel dilute magnetic semiconductors with spin-hole injection source. Highlights: Study of biaxial strain on the photocatalytic and magnetic mechanisms of Sm doping and point defects ZnO. The strains included doping, the lattice constant mismatch, and the mismatch of thermal expansion coefficient. The interstitial H increases the separation speed of electron–hole pairs, thereby prolonging the carrier lifetime. The Zn34 SmHi O36 doping system under −4% compressive strain is the best photocatalyst. The interstitial H can improve Zn34 SmHi O36 systems magnetic properties.